Social Cohesion and Religiosity – Empirical Results from an Online Survey in Germany during the COVID-19 Pandemic - Hillenbrand, Carolin (Religion & development, 2023)
The empirical results for Germany show that the people surveyed in the period from July 2020 to January 2021 tended to hold together more. Several cohesion dimensions, particularly institutional trust and national identification, strengthened. In contrast, social trust weakened. The role of religiosity is ambivalent. It is not the intensity but the content and practices of faith that make the difference. Exclusivist religious beliefs, a punitive image of God, and private prayer practice are negatively related, while a loving image of God and service attendance are positively related to social cohesion.